MGMT protein expression is a reliable predictive biomarker for temozolomide‐containing chemotherapy in osteosarcoma - Uchihara, Yoshinori; Umeda, Katsutsugu; Yamada, Yosuke; Ito, Hiroaki; Tasaka, Keiji; Isobe, Kiyotaka; Akazawa, Ryo; Kawabata, Naoko; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; Noguchi, Takashi; et al. (Cancer Science, 2024)
The prognosis of patients with osteosarcoma who experience recurrence or progression (R/P) is extremely poor, and more effective and less toxic therapies are needed. In the current study, the clinical data of osteosarcoma patients who experienced R/P were retrospectively analyzed to verify the reliability of O‐6‐methylguanine‐DNA methyltransferase (MGMT) protein expression or MGMT promoter methylation for predicting the response to off‐label temozolomide (TMZ)‐containing chemotherapy. Of the 30 evaluable patients, 9 (30%) showed no/low MGMT protein expression, whereas all 16 evaluable patients had unmethylated MGMT promoter irrespective of MGMT protein expression levels. Twenty‐three patients received TMZ‐containing chemotherapy for measurable lesions (n = 14) or as adjuvant therapy following resection of recurrent lesions (n = 9). Among 14 patients with radiologically measurable lesions, the objective response rate was higher in the MGMT no/low‐expression group (50.0%) than in the MGMT intermediate/high‐expression group with borderline significance (0%, p = 0.066). The 6‐month progression‐free survival (PFS) rate in patients with radiologically measurable lesions was significantly higher in the MGMT no/low‐expression group (50.0%) than in the MGMT intermediate/high‐expression group (0%, p = 0.036). In the multivariate analysis of the 23 patients receiving TMZ‐containing chemotherapy, MGMT expression and disease status before TMZ‐containing chemotherapy were significantly associated with PFS. No severe adverse effects were observed during TMZ‐containing chemotherapy. MGMT protein expression, but not MGMT promoter methylation, could predict a favorable outcome in patients receiving TMZ‐containing chemotherapy. Temozolomide (TMZ)‐containing chemotherapy exerts powerful and long‐lasting antitumor effects in a certain percentage of patients with osteosarcoma experiencing recurrence or progression. O‐6‐methylguanine‐DNA methyltransferase (MGMT) protein expression, but not MGMT promoter methylation, is a reliable predictor of the effect of TMZ‐containing chemotherapy.